Faktor FAKTOR YANG MENDUKUNG PENERAPAN KONSERVATISME AKUNTANSI PERUSAHAAN MANUFAKTUR DI BEI - TIFFANIA RIZKI; Deasy Ariyanti Rahayuningsih (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The aim of this paper is to empirically examine the effect of factors on the accounting conservatism in manufacturing companies listed in Indonesian Stock Exchange from 2017 until 2019. The independent variables used were institutional ownership, managerial ownership, the number of audit committee meetings, the size of board members, financial distress, leverage, and profitability. There were 82 companies selected by using purposive sampling method . The hypotheses were tested by using multiple regression analysis. The results show that the size of the board of directors, financial distress, leverage and profitability have an impact on accounting conservatism. Companies with high levels of income or profits tend to apply the conservatism to keep company profits from fluctuating. The company recognizes debts and expenses before assets and revenues and the involvement of the board of commissioners in the company to minimize the level of accounting conservatism. While institutional ownership, management ownership, and the number of audit committee meetings have no effect on the accounting conservatism.